Oficinas paleontológicas e geológicas: uma ferramenta didática para o ensino fundamental - Silva, Rosely Vaz Bernardes (2019)
In this study we present a proposal of Paleontological and Geological Workshops as a didactic tool to be used in practical classes of elementary school which will allow students to know more about rocks, fossils and geological time through didactic sequences that were applied during the research development. . The study of Geosciences (Paleontology and Geology) focusing on basic education are scarce in Brazil, for both elementary and high school. It is understood that the lack of Geosciences works leads to a learning disability and suggests the need for studies related to this theme that involves different strategies and methodologies. The present work consists of a qualitative and quantitative research, from the perspective of an in-depth study of the teaching of Geosciences, through the Geological and Paleontological Workshops, aiming to present, promote and disseminate diversified methodologies to be applied in Geological T ime workshops, Cycle of Rocks and Fossils in search of meaningful learning. The workshops were applied at various stages in three elementary schools I in the 6th grade. Data were collected through interviews, participations, questionnaires and active methodology, seeking the involvement and interest of the school communities involved in the research. In which we can make the dissemination of fossils found in Brazil and the Southwest Region of Goiás, thus reducing the lack of regionalized didactic material, by making a booklet containing didactic sequences with information and guidance for the understanding and understanding of the teaching of geosciences. In addition, we can evaluate the use of these methodologies as an important aid for teachers dealing with this subject, since the content of Geosciences present in textbooks is sometimes very complex incomplete or lacking in conceptual errors.